A thematic analysis of osteopathic physicians` identities and experiences in north american professional sports - Blacha, K.; Cade, A.; Russell, T.; Skinner, D. (Open Access Journal of Sports Medicine, 2022)
Objective This interview-based thematic analysis examines the evolving professional identities and practices of osteopathic physicians (DOs) in North American professional sports (baseball, basketball, football, hockey, and soccer) to understand the extent to which DOs employ osteopathic-specific skill sets in their work with player-patients. In addition, the study sought to understand the prevalence of professional bias, interprofessional dynamics between DOs and other health professionals, and other factors such as management.